IMPLEMENTASI PERANAN SATUAN POLISI PAMONG PRAJA DALAM MELAKUKAN PENGAWASAN KAWASAN TANPA ROKOK - Sulviko, Angga; Arman, Zuhdi (SCIENTIA JOURNAL, 2020)
In the City of Batam the Enforcement of Regional Laws is regulated in Regional Regulation No. 1 of 2016 concerning No-Smoking Areas. In Article 3 the stipulation of KTR aims to provide protection from the dangers of cigarette smoke for passive smokers, families, communities and the environment. Even though there is already a regulation that regulates everything that is related, there is still a violation. This research was conducted in order to find out how the role of the Civil Service Unit in supervising No-Smoking Areas according to Regional Regulation No. 1 of 2016 concerning No-Smoking Areas. And what are the obstacles and efforts made by the Civil Service Unit. In this study the authors used a judicial approach to empirical juridical approach with descriptive analytical research. From the results of the research, it can be seen that First, in Article 3, Article 5, and Article 27, it is clear that there is a prohibition against smoking, selling, and sanctions. A total of 62 cases occurred in 2018 until 2019. Second, the obstacle faced by the Civil Service Unit was that there were many interventions from the people who felt it was their right to smoke. Third, the efforts made by the Civil Service Unit to provide more insight to the community about the impact they have on passive smokers and impose severe sanctions on violators. It can be concluded that the role of the Civil Service Unit is not optimal because there are still many people who do not know about the prohibition of No-Smoking Areas.